2013
DOI: 10.4081/jae.2013.381
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic issues in ewe cheese production: reliability of the Strain Index and OCRA Checklist risk assessments

Abstract: Occupational ergonomists often use a variety of methods to identify jobs that are considered at high risk for the development of work-related musculoskeletal illnesses. The Strain Index (SI) and the Occupational Repetitive Actions (OCRA) Checklist are two popular upper limb risk assessment tools used in many industries, including the agro-food industry. Both methods are based on similar biomechanical, physiological and epidemiologic principles, but their approach to quantification and estimation of risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Some studies compared the raw scores, while others compared the scores for the risk of MSCs. Similar to our results, those of one study revealed moderate to strong correlations and agreement between the SI and OCRA checklist scores ( r = 0.94, kappa 0.76) [ 47 ]. Another study found that high SI scores were associated with high RULA scores in 75% of the cases [ 45 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Some studies compared the raw scores, while others compared the scores for the risk of MSCs. Similar to our results, those of one study revealed moderate to strong correlations and agreement between the SI and OCRA checklist scores ( r = 0.94, kappa 0.76) [ 47 ]. Another study found that high SI scores were associated with high RULA scores in 75% of the cases [ 45 ].…”
Section: Discussionsupporting
confidence: 91%
“…In this part of the study four observation-based methods were compared together with the DOT and UEWD-R. To the best of our knowledge, not one study has compared all these methods before. Previous studies compared two or three observation-based methods for assessing physical work demands on the upper extremities (SI versus RULA [ 45 ], TLV for HAL versus SI and OCRA [ 46 ], SI versus OCRA [ 47 ], and TLV for HAL versus OCRA [ 48 ]). The results of these studies differed because of the use of different methods.…”
Section: Discussionmentioning
confidence: 99%